INVENTARISASI BAHAN PEWARNA ALAMI PADA TENUN CORAK INSANG SEBAGAI SUMBER BELAJAR BIOLOGI - Liyu Vani Aji Airlangga; Hanum Mukti Rahayu; Ari Sunandar (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The gill-pattern woven fabric is a traditional textile originating from Pontianak City. However, the use of chemical dyes in the dyeing process has negative impacts on the environment. As a result, natural dyes have regained popularity due to their environmentally friendly properties. Natural dyes are generally derived from various plant parts, such as wood, bark, roots, root bark, seeds, seed coats, leaves, and flowers.Â Â This study employed a descriptive research design with an exploratory approach, aiming to collect data on the types of plants used in producing natural dyes for gill-pattern woven fabrics. Data were collected through interviews with traditional weaving artisans in Batulayang Village, Gang Sambas. The research also included the documentation and inventory of natural dye sources used in the past. The findings showed that the gill-pattern woven fabric has great potential as a local learning resource, with a feasibility percentage of 93.5%. Furthermore, eight plant species were identified as traditional sources of natural dyes historically used in the weaving process. These results highlight the cultural and educational value of gill-pattern weaving and the potential of natural dyes in supporting sustainable textile production.